Pembuatan Pulp Cetak Tanpa Perekat Dari Pulp Batang Jagung - Muhammad S. A. Aziz; Zulfansyah Zulfansyah; Warman Fatra; Hari Rionaldo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Packaging material’s demand continue to increase along with the development of industry all over the world. Styrofoam as conventional packaging materials, have been looked for a subtitute because it does not decompose and the depletion of fossil fuels as it’s feedstock. Cornstalk has abundant amount as biomass waste. Despite it’s well known quality as raw material for pulp, it hasn’t got utilized yet. Molded pulp as one of the alternative packaging, has a promising future with it’s degradable characteristics and good mechanical properties. Cornstalk as raw material for the pulp along with the empty fruit bunch (EFB) ash works as the alkaline source for the alkaline pulping. The binderless molded pulp then formed with the help of hot press. The thermoset properties of the lignin itself, give the posibility to produce molded pulp without any binder resin. Tensile index, tear index and burst index were determined experimentally to express the mechanical properties of the binderless molded pulp products. This experiment were done as an effort to utilize the biorenewable resource to make a packaging product that could be an alternative to the conventional one.The result indicate that cornstalk as raw material to produce molded pulp gives good mechanical properties compare to styrofoam packaging product. Molded pulp from cornstalk gives tensile index 17,5 – 34 Nm/g, tear index 10 – 26 mN.m2/g and burst index 0,89 – 1,52 kPa.m2/g. In generally, variation of temperature give dominant significant influence to mechanical properties of molded pulp.Keywords: Binderless; Cornstalk; EFB Ash; Packaging; Molded Pulp